2005
DOI: 10.1111/j.1471-4159.2005.03056.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cholesterol/lipid biosynthetic genes by Egr2/Krox20 during peripheral nerve myelination

Abstract: Myelination of peripheral nerves by Schwann cells requires a large amount of lipid and cholesterol biosynthesis. To understand the transcriptional coordination of the myelination process, we have investigated the developmental relationship between early growth response 2 (Egr2)/Krox20 -a pivotal regulator of peripheral nerve myelination -and the sterol regulatory element binding protein (SREBP) pathway, which controls expression of cholesterol/lipid biosynthetic genes. During myelination of sciatic nerve, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 76 publications
5
89
0
1
Order By: Relevance
“…49 To our knowledge, there is no specific studies so far about the impact of the SREBP pathway in myelination in the central nervous system, but several studies have demonstrated the importance of this pathway in the peripheral myelination of axons. 50,51 The present implication of SREBF1 and SREBF2 as genetic susceptibility factors in schizophrenia further underscores the importance of lipid biosynthesis and myelination in the pathophysiology of schizophrenia.…”
Section: Abnormalities In Myelination and Lipid Biosynthesis In Schizmentioning
confidence: 86%
“…49 To our knowledge, there is no specific studies so far about the impact of the SREBP pathway in myelination in the central nervous system, but several studies have demonstrated the importance of this pathway in the peripheral myelination of axons. 50,51 The present implication of SREBF1 and SREBF2 as genetic susceptibility factors in schizophrenia further underscores the importance of lipid biosynthesis and myelination in the pathophysiology of schizophrenia.…”
Section: Abnormalities In Myelination and Lipid Biosynthesis In Schizmentioning
confidence: 86%
“…In all of this, Pax-3 resembles c-Jun and Sox-2. Paradoxically, however, in early postnatal nerves of Krox-20 null or heterozygous mice, Pax-3 mRNA levels are lower than in control nerves (Leblanc et al, 2005). In adult nerves, Pax-3 is also upregulated after nerve transection, but it is not known whether it is involved in the control of dedifferentiation.…”
Section: Pax-3mentioning
confidence: 95%
“…In the case of myelinating cells this involves downregulation of a large number of genes related to myelination (reviewed in Jessen and Mirsky, 2005;Mirsky et al, 2008;Scherer and Salzer, 2001). This includes enzymes that provide for cholesterol synthesis, structural proteins such as P 0 , myelin basic protein (MBP), and membrane associated proteins such as myelin associated glycoprotein (MAG) and periaxin (Buchstaller et al, 2004;D'Antonio et al, 2006;Leblanc et al, 2005;Nagarajan et al, 2001Nagarajan et al, , 2002Verheijen et al, 2003). This switch-off is accompanied by the activation of another group of molecules, most of which are normally found on immature cells prior to myelination.…”
Section: Schwann Cell Dedifferentiation During Wallerian Degenerationmentioning
confidence: 99%
“…Peaks of binding were localized to the transcription start site and extended into the proximal promoter and sometimes into the first exon of the gene. Cyp51 has been previously shown to be responsive to EGR regulation (14), as has Me1 (31). In addition to these genes, Egr1 binding was identified in the promoters of the HMG-CoA synthase (Hmgcs), farnesyl diphosphate synthase (Fdps), farnesyldiphosphate farnesyltransferase 1 (Fdft1), lanosterol synthase (Lss), sterol-4␣-carboxylate 3-dehydrogenase (Nsdhl), and malic enzyme (Me1) genes (see supplemental Fig.…”
Section: Egr1 Localizes To the Promoters Of Several Genes In The Cholmentioning
confidence: 99%
“…Accordingly, we have shown that Egr2 can act synergistically with SREBP-2 to activate transcription of the promoters of certain cholesterol biosynthetic genes (e.g. Hmgcr) (14). Additionally, in the Krox20/Egr2 null mouse, the expression of Hmgcr and Cyp51 was significantly reduced (Ͼ80%) in peripheral nerve despite little change in SREBP levels, suggesting a role for EGR factors in the regulation of cholesterol metabolism.…”
mentioning
confidence: 92%